Development of a creative digital curriculum for the elderly: A participatory approach to enhance potential for alternative career opportunities in the digital era - Saisee, Parit; Supachant, Sukontip; Patthanaphong, Omthong; Limphaiboon, Jaruwan; Fongkanta, Pongwat (Asian Journal of Education and Training, 2024)
This research aimed to develop a curriculum for empowering the elderly to create alternative careers in the digital society era through digital platforms and to study the effects of the curriculum and online educational channels on enhancing the elderly’s capabilities. Participatory Action Research (PAR) methods combined with qualitative and quantitative approaches were employed in this study. The study involved 555 participants including personnel and elderly individuals in Lampang Province that were selected by using multi-stage sampling. Descriptive statistics were used to analyze the data and compare the group mean by t-test. The research findings revealed that the “Creative Digital Retirees” curriculum for empowering the elderly to use digital technology, digital media literacy and utilizing digital media to create alternative careers met the effective criteria, the 80/80 efficiency criteria with E1 = 80.00 and E2 = 87.16. The effective curriculum consists of five learning units including Unit 1: Using technology media for the elderly, Unit 2: Understanding and digital literacy for the elderly, Unit 3: Creating social media for the elderly, Unit 4: Accessing, efficient use of technology and technology management for the elderly, and Unit 5: Electronic law. The elderly’s capabilities significantly improved at a significance level of 0.05. For curriculum users’ satisfaction, the result showed the highest level of satisfaction with an average score of 4.59. It is concluded that the curriculum is effective and can genuinely enhance the elderly’s learning achievements.